Raw Potato Starch Alters the Microbiome, Colon and Cecal Gene Expression, and Resistance to Citrobacter rodentium Infection in Mice Fed a Western Diet. (14th June 2022) - Smith, Allen; Chen, Celine; Cheung, Lumei; Ward, Robert; Hintze, Korry; Dawson, Harry
Abstract: Objectives: To evaluate the effects of feeding a Total Western Diet (TWD) based on NHANES data containing 0, 2, 5 or 10% raw potato starch on the microbiome, gene expression, and resistance to Citrobacter rodentium infection in mice. Methods: 3–4 week old C57Bl/6 mice were fed the TWD for 6 weeks followed by 3 weeks of the TWD containing 0, 3, 5, or 10% raw potato starch (RPS). Mice were euthanized and tissues collected for analysis. In other experiments, after 3 weeks on the RPS containing diets, mice were infected with Citrobacter rodenitium (Cr), mice euthanized at day 12 post-infection and tissues collected for analysis. DNA isolated from cecal or fecal contents was used for sequencing of the V3-V4 hypervariable regions of the 16S rRNA gene. For gene expression analysis, RNA isolated from colon and cecal tissues was sequenced on an Illumina HiSeq 4000 using a 1 × 50 bp single end format. Results: Feeding the RPS diets resulted in changes to the microbiome with α-diversity decreasing with increasing levels of dietary RPS (p < 0.05). PCA analysis showed four discreet groupings based on the RPS level that were significantly different by 0.5 Unifrac PERMANOVA analysis (p < 0.001). The relative abundance of various genera was altered by feeding increasing levels of RPS. The genus Lachnospiraceae NK4A136 group was markedly increased in a dose-dependent fashion. Differential expression of the genes was highest in the cecum but decreased substantially in the proximal colon and further so in the distal colon. The pattern of gene expression observed suggest that RPS primes the intestine for immune responses to bacteria, parasites and viruses. However, mice fed the 10% RPS diet and infected with Cr had increased colonization of the colon at day 12 post-infection that was not observed at lower levels of dietary RPS (p < 0.05). Mice had increased hyperplasia and colonic pathology in the 10% RPS group compared to mice receiving diet without added RPS. 16S sequencing of cecal contents showed RPS-dependent changes in both uninfected and infected mice. Conclusions: Dietary RPS significantly altered the microbiome of mice in the context of a NHANES-based Western Diet. Mice fed diets containing 10% RPS had significant changes in cecal and colon gene expression, Cr colon colonization and infection-induced pathology. Funding Sources: USDA ARS.